Commentary on Tripp's "Comparative perspectives on concepts of gender, ethnicity, and race". (2nd April 2016) - Decker, Alicia C.
Abstract : Aili Tripp's research utilizes a comparative historical framework to analyze why strategies promoting women's rights, political power, and peace have worked in some contexts but not in others. Much depends on whether a given culture views gender relations in terms of "equality" or "difference." Those societies which value equality within gender relations tend to emphasize diversity and the importance of identity, particularly in terms of racial and ethnic difference among women, while those which focus upon difference—the idea that women are inherently different from men—emphasize similarities among women as a group. Although this typology is valuable, it does not work well in all historical contexts. In this essay, I focus on Africa and some of the limitations of using "difference" to understand African women's empowerment.